Persistency and Money Demand Distortions in a Stochastic DGE Model with Sticky Prices - Michael Gail (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2001)
Recently macroeconomists have intensified their efforts to develop models that are able to generate persistent reactions of real variables to monetary shocks in stochastic DGE models with nominal rigidities. This has proven to be quite difficult in models with price staggering only. Most papers show that output is above steady state only as long as prices are fixed for the firms. In this article particular attention is given to the role of money demand and to the form of the utility function. I consider cash-in-advance- (CIA) as well as money-in-the-utility-function- (MIU) models, with CRRA and GHH preferences, to evaluate their ability to generate persistence. Persistent reactions emerge only with a high value of the elasticity of labor supply with respect to the real wage and an interest rate sensitive money demand function. CIA-models generally create more persistency than MIU-models. In the CIA-setup a CRRA utility function generates more persistence than GHH preferences. The results highlight the importance of the way money is introduced in a New Neoclassical Synthesis model.
Keywords: E52; 330; Monetary Policy; New Neoclassical Synthesis; Sticky Prices; Persistency; Neue klassische Makroökonomik; Geldnachfragetheorie; Real Business Cycle; Preisrigidität; Dynamisches Gleichgewicht; Geldpolitik; Schock; Hysteresis; Theorie; Makroökonomischer Einfluss